Use of thyroid hormones in hypothyroid and euthyroid patients: a 2020 THESIS questionnaire survey of members of the Czech Society of Endocrinology - Jiskra, Jan; Paleček, Jan; Attanasio, Roberto; Hegedüs, Laszlo; Nagy, Endre V; Papini, Enrico; Perros, Petros; Negro, Roberto; Kršek, Michal (BMC endocrine disorders, 2022)
BACKGROUND: Inconsistencies in the management of hypothyroidism have been reported among endocrinologists in different European countries. Aim of this study was to explore Czech endocrinologists' use of thyroid hormones in hypothyroid and euthyroid patients. METHODS: We used a web-based survey containing 32 questions regarding the use of thyroid hormones. Four-hundred thirty-two members of the Czech Society of Endocrinology received an e-mail invitation to participate in the survey. RESULTS: We received and analysed 157 responses (112 females and 45 males) from the 432 members (36.3%). According to 99.4% of the respondents, levothyroxine (LT4) is the primary drug of choice for the treatment of hypothyroidism. Liothyronine (LT3) was used in clinical practice by 29.9% of responders. According to 90.5% of respondents, thyroid hormones may be indicated in biochemically euthyroid patients. Female physicians prescribe thyroid hormones in euthyroid infertile women with high antibody levels more frequently than male physicians (P = 0.003). Most Czech endocrinologists (76.4%) consider combined therapy with LT4 and LT3 in various clinical scenarios, but only 1 of 29 hypothyroid physicians (3.5%) would recommend it to their patients, and only 4 out of 128 respondents (3.1%) would consider LT3 or desiccated thyroid for themselves, if diagnosed with hypothyroidism. CONCLUSION: LT4 is the primary thyroid hormone used in the Czech Republic for treatment of hypothyroidism. At variance with thyroid guideline recommendations, Czech endocrinologists are quite liberal when prescribing thyroid hormones to euthyroid patients and in the use of LT4/LT3 combination treatment for hypothyroid patients with persisting symptoms.
Keywords: Surveys and Questionnaires; Humans; Survey; Female; Euthyroidism; Hypothyroidism; Thyroxine; ženská infertilita; Infertility, Female; lidé; průzkumy a dotazníky; hypotyreóza; ženské pohlaví; Male; Levothyroxine; Czech Republic; thyroxin; Liothyronine; Česká republika; mužské pohlaví